Motor Imagery Development in Children: Changes in Speed and Accuracy With Increasing Age - Souto, Deisiane Oliveira; Cruz, Thalita Karla Flores; Fontes, Patrícia Lemos Bueno; Batista, Rodrigo Caetano; Haase, Vitor Geraldi (Frontiers in Pediatrics, 2020)
Although motor imagery has been pointed as a promising strategy for the rehabilitation of children with neurological disorders, information on their development throughout childhood and adolescence is still scarce. For instance, it is still unclear at what age they reach a development comparable to the motor imagery performance observed in adults. Herein we used a mental rotation task to assess motor imagery in 164 typically developing children and adolescents, which were divided into four age groups (6-7 years, 8-9 years, 10-11 years, 12-13 years) and 30 adults. The effects of biomechanical constraints, accuracy and reaction time of the mental rotation task were considered. ANOVA showed that all groups had the effect of biomechanical restrictions of the mental rotation task. We found a group effect for accuracy (F [4,180] = 17,560; p <0.00; η² = 3.79) and reaction time (F [4,180] = 17.5; p <0.001, η² = 0.615), with the results of children groups 6-7 years and 8-9 years being significantly lower than the other groups (p <0.05). In all the analyses, there were no differences regarding accuracy and reaction time among the participants of the age groups 10-11 and 12-13 years and adults (p> 0.05). Concluding, children aged 6-7 years were able to perform motor imagery, motor imagery ability improved as the participants' ages increased, and children aged 10 and over-performed similarly to adults.